History and memory in African-American culture - Fabre, Geneviève; O'Meally, Robert G., 1948- (Oxford University Press, 1994)
The relation between history and memory has become an object of increasing attention among historians and literary critics. Through a team of leading scholars, this volume offers a complex picture of the dynamic ways in which an African-American historical identity constantly invents and transmits itself in books, art, performance, and oral documents.
Keywords: African Americans -- History.; African Americans -- Historiography.; African American arts.; American literature -- African American authors.; Noirs américains -- Histoire.; Noirs américains -- Historiographie.; Arts noirs américains.; SOCIAL SCIENCE -- Ethnic Studies -- African American Studies.; African American arts; African Americans; African Americans -- Historiography; American literature -- African American authors; Geschichte; Geschichtsschreibung; Kultur; Literatur; Schwarze; USA; Aufsatzsammlung; Schwärze; Historisch besef.; Geschiedschrijving.; Zwarten.; Écrivains noirs américains -- États-Unis.; Arts noirs américains -- États-Unis.; Art noir américain.; Littérature américaine -- Auteurs noirs américains.; Geschichte 1800-1990.; Black persons -- Culture -- History; United States; History